Sosialisasi dan Demonstrasi Ramuan Tradisional Untuk Menjaga Imunitas Tubuh Selama Pandemi Covid-19 - Oktaviana, Maulida Nurfazriah; Nuzula, Firdawsyi (PPPM Stikes Banyuwangi, 2022)
Background: In the community's efforts to maintain health in the era of the Covid-19 pandemic, there are several choices that can be made, namely by eating lots of nutritious food, diligently exercising and consuming traditional plants or herbs. Traditional herbs are one of the local wisdoms passed down from generation to generation from our ancestors, easy to get and have significant opportunities to be used as preventive efforts in maintaining immunity. It seems that almost every resident's house has medicinal plants in their yards and yards, but very few of them know their use to prevent Covid-19. The purpose of PkM is to increase public knowledge about herbal plants around, and improve community skills in making traditional ingredients. The target audience of PKM is a group of women who have herbal plants and are willing to be given information on the benefits of herbal plants and mix or make traditional ingredients. Method: The PkM method is to see the problems faced by partners, the steps taken to achieve the goals and objectives of this activity are health education to increase knowledge, providing examples of how to make traditional ingredients, which will be guided by the implementing team, namely the lecturer from the Rustida Banyuwangi Health Academy. alone. Results: The results of community service that have been carried out for mothers so that they can make traditional ingredients at their respective homes to increase immunity. On average, mothers have herbal plants in their yards as much as 64%, mother's knowledge increases to 68%. Conclution: for the community, especially mothers, can be more creative in utilizing traditional plants in their yard